Corporate social responsibility: The involvement of small medium enterprises - Atan, Ruhaya; Ahmad Shukri, Nor Fadhilah; Zainon, Saunah (2015)
The purpose of the paper is to study the involvement of corporate social responsibility by small medium enterprises (SMEs) in Malaysia. Based on the sample taken from SMEs listed under Enterprise 50 (E50) over five years, questionnaires were distributed to find out their involvement in CSR and their motivation for engaging in CSR activities.For this purpose Carroll’s Pyramid of CSR was used as the framework.It was found that that majority of the SMEs involved in ethical responsibility, followed by legal responsibility, economic responsibility and lastly, philanthropic responsibility.It showed that ethical responsibility as the foundation of CSR involvement by Malaysian SMEs and this result is contrary to Carroll’s Pyramid of CSR.The findings also reveal the SMEs were motivated firstly by their own beliefs and values, followed by religious thought and that CSR may enhance the company’s reputation.This motivation is in line with their emphasis on ethical responsibility when engaged in CSR. This study contributes to knowledge about CSR by small medium enterprises, which is still lacking in the literature on CSR, particularly in Malaysia.